A new perspective on Singapore’s environmental history : the history of Singaporeans’ environmental consciousness since 1965 - Tan, You Yi (2016)
This paper is interested in the presence and contribution of Singaporeans in Singapore’s environmental journey and will attempt to address the following key question. Besides the governmental efforts, have Singaporeans been as proactive in contributing to the state of their clean, green living environment and has there been an extensive rise in their environmental consciousness over the years since 1965? This paper will argue that there has been a gradual but limited rise in Singaporeans’ environmental consciousness over the decades. Environmental consciousness of Singaporeans is defined here as their keenness to “translate awareness ” of local, regional and global environmental issues into environmentally-friendly efforts including “simple, everyday ” actions such as participating in recycling programmes and not littering that can be readily applied to Singapore’s unique clean and green environment. This paper will examine three key areas. First, it will address Singaporeans’ environmental engagement through opinion letters, feedback and views. Second, it will examine Singapore’s public and school environmental education, youths, and simple, everyday actions including Singaporeans’ littering behaviour and their recycling efforts. Last, it will also examine Singaporeans’ participation in environmental non-governmental organizations (NGOs) and green groups.